Analisis Proses Pembelajaran Matematika Siswa Tunarungu di Sekolah Inklusi - Tri Astutiningsih; Fadhilah Rahmawati; Aprilia Nurul Chasanah (Pendidikan Matematika UNIMOR, 2023)
Inclusive schools are organized by the government in order to provide opportunities to all students regardless of conditions and backgrounds. Deaf as individuals who have barriers and special needs are still discriminated against so that they cannot study in inclusive schools due to lack of facilities and knowledge of the learning process of deaf students, especially mathematics subjects. The purpose of this study was to analyze the implementation and obstacles to the mathematics learning process of deaf students in inclusive schools. The method used is a qualitative descriptive research method. The results of the research obtained include: 1) at the learning planning stage mathematics teachers maked unit planners while shadow teacher maked IEP; 2) at the stage of learning implementation the learning system given to deaf students is the same as other regular students, mathematics teachers used clear lip gestures in explaining, and deaf students was accompanied by shadow teacher during the learning process; 3) at the evaluation stage, the evaluation questions given to deaf students was the same as other regular students; 4) GPK is constrained in how to explain the material to deaf students, set strategies in providing motivation and providing consequences when deaf students are lazy, and teachers must be ready to re-explain the material that has been delivered. Keywords: Mathematics Learning Process, Deaf Students, Inclusion School